Note sur la découverte d’un petit monument funéraire à proximité d’une villa, à La Chapelle-Vendômoise (Loir-et-Cher) - Fabrice Couvin; Marielle Delémont; Alexandre Fontaine; Philippe Gardère (Revue Archéologique du Centre de la France)
A recent archaeological diagnostic on the commune of La Chapelle-Vendômoise (Loir-et-Cher, France) has revealed a small roman funerary monument. Largely razed and recuperated, it can be connected with a villa excavated nearby. This construction gives indications about the social status of its owners and attests the adoption of a funeral architecture of Mediterranean tradition in this rural territory. This discovery is part of a largely structured landscape, with the proximity of a roman road associated with rural settlements. It is also the opportunity to make an initial inventory of the different types of funerary architecture found in the Centre-Val de Loire during the High Empire.